A ratiometric AIE probe for dual color imaging lipid droplets and lysosomes and real-time quantitative monitoring lipophagy. (December 2022) - Zhuang, Jiabao; Yu, Yiyi; Su, Rouan; Ma, Qijia; Li, Nan; Zhao, Na
Abstract: Lipophagy, one of the interactions between lipid droplets (LDs) and lysosomes, is essential for maintaining intracellular homeostasis. In this work, a pH-sensitive ratiometric fluorescent probe (LD-L) with aggregation-induced emission (AIE) characteristics was developed to simultaneously stain LDs and lysosomes with dual-color emission and to real-time quantitatively monitor the lipophagy process. LD-L was constructed by introducing a proton accepter of N, N ′-diethylamino unit into AIE-active pyrazoline-based skeleton. Upon protonation, bright emission at 570 nm of LD-L blue shifted to 475 nm, resulting in a significant ratiometric fluorescent response towards pH change. A good linear relationship between fluorescent intensity ratio ( I 475 / I 570 ) and pH range of 4.85–5.05 was obtained while the pKa of LD-L was determined to be 4.97. Importantly, LD-L could simultaneously stain the LDs and lysosomes with different emission under single 405 nm excitation and image the intracellular pH with a ratiometric fluorescence mode. LD-L was further applied to real-time monitor lipophagy process and to quantify the pH change of LDs at later stage of lipophagy. Graphical abstract: Image 1 Highlights: LD-L exhibited typical aggregation-induced emission effect and ratiometric response towards pH change. LD-L simultaneously stains the LDs and lysosomes with different emission under single 405 nm excitation. LD-L can real-time monitor lipophagy process and quantify the pH change of LDs at later stage of lipophagy.